Combined Idiopathic Macular Hole Vitrectomy with Phacoemulsification without Face-Down Positioning - Fumihiko Yagi; Seiji Takagi; Goji Tomita (Journal of Ophthalmology)
Purpose. To evaluate the outcome of combined vitrectomy with phacoemulsification without postoperative face-down positioning for idiopathic macular holes (MHs). Design. Retrospective, observational case series. Participants. Forty-two eyes of 42 patients with MH. Methods. We studied 42 eyes of 42 cases followed up for 6 months postoperatively. MH closure rate and preoperative and postoperative visual acuity (VA) were evaluated. Main Outcome Measures. MH closure rate and VA were evaluated after combined vitrectomy with phacoemulsification without postoperative face-down positioning. Results. Of the 42 holes, 40 (95.2%) were initially closed, and the final closure rate was 100%. Compared with preoperative VA, the mean VA was significantly improved at 1 month and the improvement was maintained for at least 6 months postoperatively. Conclusions. Combined vitrectomy with phacoemulsification without postoperative face-down positioning produced favorable anatomic and functional results for MH repair. Improvement in VA can be expected for up to at least 6 months postoperatively.